An exploratory study of the 'creativity toolbox' as a teaching tool to promote creativity in learning. - Paken, Shakti (My University, 2015)
The intention of presenting this article on the use of the creativity toolbox, which has been used to explore creativity in teaching and learning which assists educators in, fostering student engagement and student centeredness in the class room . The article further aims to present information on the monitoring and evaluation of the use of the creativity toolbox during lesson planning, classroom activities and behavior management. The research project was prompted due to the lack of poor concentration and literacy levels that contribute to a lack of classroom engagement within the Public Relations Practice module. The research aims to encourage active learning via various teaching strategies such as the use of the creativity toolbox. This proactive approach is linked to the constructive approach to encourage students to interact with content and tools in a creative way that shapes content into learning, knowledge and understanding. The findings of the research present the use of the creativity toolbox emphasising the learning experience in the classroom. Students enjoyed lessons being planned to accommodate a style of learning that catered to their understanding by assisting them absorb content and made the lesson interactive. This study aims to provide a contribution to teaching strategies in a higher educational classroom amongst many different levels of students.
Keywords: Lesson planning; Creativity toolbox; Teaching strategies